Toll like receptor 2, 4, and 9 signaling promotes autoregulative tumor cell growth and VEGF/PDGF expression in human pancreatic cancer - Grimmig, Tanja Maria; Rückert, Felix (International journal of molecular sciences, 2016)
Toll like receptor (TLR) signaling has been suggested to play an important role in the inflammatory microenvironment of solid tumors and through this inflammation-mediated tumor growth. Here, we studied the role of tumor cells in their process of self-maintaining TLR expression independent of inflammatory cells and cytokine milieu for autoregulative tumor growth signaling in pancreatic cancer. We analyzed the expression of TLR2, -4, and -9 in primary human cancers and their impact on tumor growth via induced activation in several established pancreatic cancers. TLR-stimulated pancreatic cancer cells were specifically investigated for activated signaling pathways of VEGF/PDGF and anti-apoptotic Bcl-xL expression as well as tumor cell growth. The primary pancreatic cancers and cell lines expressed TLR2, -4, and -9. TLR-specific stimulation resulted in activated MAP-kinase signaling, most likely via autoregulative stimulation of demonstrated TLR-induced VEGF and PDGF expression. Moreover, TLR activation prompted the expression of Bcl-xL and has been demonstrated for the first time to induce tumor cell proliferation in pancreatic cancer. These findings strongly suggest that pancreatic cancer cells use specific Toll like receptor signaling to promote tumor cell proliferation and emphasize the particular role of TLR2, -4, and -9 in this autoregulative process of tumor cell activation and proliferation in pancreatic cancer.